From stem to steam : brain-compatible strategies and lessons that integrate the arts - Sousa, David A.; Pilecki, Tom (California : Corwin, 2018)
"STEAM the integration of music, visual arts, and drama into daily STEM instruction is proven to enhance student achievement in STEM subjects. After all, creative, real-world problem-solving is what working scientists and mathematicians actually do. But how do busy STEM educators weave arts activities into a sometimes inflexible STEM curriculum? In this new edition the authors provide lessons from the field to detail the way."--Publisher's promotional description.
1. Why STEM should brcapome STEAM -- 2. What science says about the arts and creativity -- 3. Bringing STEAM into schools -- 4. Guidelines for creating a STEAM school -- 5. Frequently asked questions about integrating the arts and STEM -- 6. Implementing arts integration in the primary grades (K-4) -- 7. Implementing arts integration in the intermediate grades (5-8) -- 8. Implementing arts integration in the high school grades (9-12) -- 9. Discoveries from the field -- 10. Putting it all together -- Appendix A: STEAM lesson plan appetizers in science, technology, and engineering -- Appendix B: STEAM lesson plan appetizers in mathematics.
Includes references and index.
Keywords: Arts -- Study and teaching; Art in education